DEMOGRAPHIC PROFILE AND CT-MRI CHARACTERISTICS OF BRAIN METASTASIS PATIENTS AT Dr SAIFUL ANWAR HOSPITAL: A RETROSPECTIVE STUDY - Sakdullah, Istianah; Yueniwati, Yuyun (International Journal of Radiology and Imaging, 2025)
Brain cancer is one of the top ten causes of mortality globally and is classified as a malignant condition. An essential aspect of assessing the stage of malignancy when brain metastases occur is radiologic examination. Research on the demographic characteristics and CT-MRI imaging of cancer patients with brain metastases in Malang City is still limited; therefore, this study was conducted at Dr. Saiful Anwar Hospital. This study employed descriptive observational research methods, with the population consisting of patients diagnosed with brain metastatic tumors as recorded in medical records from June 2023 to May 2024. Data collection was based on secondary data obtained from medical records and the Radiology Information System (RIS). The data will be analyzed descriptively and presented in tabulated form using the SPSS program. Research on brain metastases in 92 patients revealed that the majority were aged between 41 and 70 years, had a median age of 51 years, and women were more likely to have it. Brain metastases were most frequently caused by lung cancer, then breast cancer. Metastases were most commonly found in the supratentorial region, particularly in the frontal lobe, with most patients having multiple nodules. Intratumoral hemorrhage occurred in more than half of the patients, especially those with aggressive lung cancer. Additionally, 8.3% of patients had leptomeningeal metastases.